Addressing India’s Nutrition Challenges Report of the Multistakeholder Retreat - Planning Commission (Planning Commission, 2010)
Nutrition is crucial for the fulfilment of human rights - especially those of the most vulnerable children, girls and women, locked in an intergenerational cycle of multiple deprivation. It constitutes the foundation for human development, by reducing susceptibility to infections, reducing related morbidity, disability and mortality, enhancing cumulative lifelong learning capacities, and adult productivity. It is critical to prevent under nutrition, as early as possible, across the life cycle, to avert irreversible cumulative growth and development deficits that compromise maternal and child health and survival, achievement of optimal learning outcomes in education and gender equality.
Planning Commission Government of India
Planning Commission Government of India